‘Prosperity theology’: Poverty and implications for socio-economic development in Africa - Williams, Dodeye U. (HTS Teologiese Studies / Theological Studies, 2022)
Poverty is a complex subject in traditional African cultures. It is the lack of provision to satisfy the basic human needs of the population. The prosperity gospel as part of Pentecostal Christianity, with origins in the United States of America, presents itself as a new model for poverty eradication. Pentecostal Christianity and the proliferation of Pentecostal churches in Africa, many of whom are adherents of prosperity theology over a period of more than three decades, have not translated to a more prosperous continent, and sub-Saharan Africa is still notably one of the poorest regions of the world. Poverty is a concept with many dimensions that attempts to ascertain the varying degrees of deprivation experienced by populations, individually or collectively. However, certain subjective and sometimes arbitrary interpretations of biblical texts on prosperity as the basis for prosperity theology have encouraged capitalist impulses that often supplant the pursuit of spiritual advantages, leading instead to an increase in crimes including robbery, financial fraud, kidnapping, ritual killings and many other social vices. This article examines the different perspectives of the prosperity gospel, the biblical sources and interpretations used as well as its interpretation of poverty. It shows how prosperity theology, with its own interpretation of poverty, erodes the valuable indigenous resources available to fight poverty within African religious communities, which emphasise community, positive family attachments, social support networks, moral values and accountability, and it examines the implications this has for socio-economic development in Africa. Contribution: This article challenges the theology of prosperity that characterises Pentecostal Christianity and is pervasive in Africa. It contributes to the discourse on how the challenges of poverty require the more community-centred approaches that traditional African values offer as against the self-centredness and greed promoted by the prosperity theology.
free